Pengaruh Personal Attitude dan E-learning terhadap Minat Berwirausaha pada Era Pandemi Covid-19 - Shita Lusi Wardhani; Manggar Wulan Kusuma (Universitas Proklamasi 45, 2021)
The Covid-19 outbreak and the enactment of restrictions on community activities have had many impacts, one of which is the change in teaching methods from offline learning or face-to-face activities to online learning or distance learning. These changes can affect the learning process, especially subjects related to business practices, such as entrepreneurship. In online learning, several factors contribute to the successful delivery of online courses. However, little is known about the impact of these factors on Indonesian students' interest in entrepreneurship. Therefore, the purpose of this study was to examine the effect of personal attitude and e-learning on interest in entrepreneurship in the Covid-19 pandemic era. Data was collected through an online survey of 190 students who were taking entrepreneurship courses at selected universities in Yogyakarta. Data collected through online surveys were analyzed using Smart Partial Least Square (SmartPLS) 3.0. The results of this study found that interest in entrepreneurship is significantly influenced by personal attitude and e-learning. This study also found that perceived learning was not able to moderate the effect of e-learning on entrepreneurial interest.